Marketing Strategy Local Product "Kue Bangkit Fafin" in Serang - Nur Bhakti Pertiwi, Widya; Putri Wenang Lusianingrum, Farah; Johan Widikusyanto, Muhammad (Management Science Research Journal, 2024)
Marketing strategy moment This hold important role​ in reach objective A business . The purpose of study This that is For know marketing strategies What should​ carried out by entrepreneurs local product Kue Bangkit Fafin . Study This nature descriptive qualitative use SWOT analysis . Research result showing a better alternative marketing strategy​ carried out by the product local Kue Bangkit Fafin is diversification (quadrant II). A must strategy applied is use the power it has for utilise opportunity period long. Kue Bangkit Fafin should do innovation product , so own unique and visible different from competitor